Feeding Preferences of Chanos Chanos Cultivated in Urban Area - Nurlita Abdulgani; Dewi Hidayati; Muhammad Zamharir Rojafi; Jessica Oñate Pacalioga; Azizan Akmal Ristiawan (Biosaintifika: Journal of Biology & Biology Education, 2026)
The aquaculture area in the Gunung Anyar region, affected by domestic and industrial pollution, presents challenges in sustaining natural food resources for milkfish cultivation. This research aims to evaluate the feeding preferences of milkfish (Chanos chanos) in this urban aquaculture setting, focusing on their dependency on phytoplankton, zooplankton, and other resources. Stomach content analysis was performed using the gastro somatic index, preponderance index, and numerical diet composition index. The data obtained were then analyzed descriptively and quantitatively. Findings indicate a strong preference for phytoplankton (85%), with Chlorophyta as the predominant species (54%). The results highlight the planktivorous feeding habits of milkfish, classified as high-intensity feeders (Gastro Somatic Index: 1.86–2.90). The feeding preference for phytoplankton stems from a lack of zooplankton due to the presence of multiple HAB (Harmful algal blooms) species. These findings underscore the need to manage water quality and natural food availability to sustain milkfish aquaculture productivity in urban areas. This research promotes the United Nations Sustainable Development Goals (SDGs), specifically enhancing SDG 14 (Life Below Water) through the evaluation of estuarine biodiversity, advancing SDG 2 (Zero Hunger) by ensuring urban aquaculture productivity, and supporting SDG 11 (Sustainable Cities and Communities) by developing resilient urban food systems in the face of industrial limitations.